CircRNAs in extracellular vesicles associated with triple-negative breast cancer : circRNAs in extracellular vesicles associated with TNBC - Qurtam, Ashraf Ahmed (Cellular and Molecular Biology, 2025)
Triple-negative breast cancer (TNBC) is a highly aggressive cancer with distant metastasis. Accumulated evidence has demonstrated that exosomes are involved in TNBC metastasis. Elucidating the mechanism underlying TNBC metastasis has important clinical significance. Extracellular vesicles (EVs) present a promising avenue for diagnosing and treating triple-negative breast cancer (TNBC) through a technique called "liquid biopsy," offering a new wellspring of biomarkers. These tiny lipid bilayer vesicles, released by most cells, carry a diverse array of RNA molecules that can influence the behaviour of recipient cells. Among these, circular RNAs (circRNAs) have emerged as a subtype of noncoding RNAs capable of modulating gene expression by sponging microRNAs, thus playing crucial roles in various aspects of cancer development and progression, including TNBC. Despite their significance, our understanding of circRNAs involvement in TNBC remains incomplete. However, studies have shown that circRNAs are abundant in EVs, with exosomal circRNAs (exo-circRNAs) particularly influential in cancer biology. These exo-circRNAs can be taken up by neighboring or distant cells, impacting numerous aspects of their physiological states, thereby enhancing cell communication and tumor dissemination. This review provides an overview of EVs key characteristics and functions before delving into exo-circRNAs potential roles in driving or suppressing TNBC, as well as their implications for cancer diagnosis, prognosis, and monitoring.